Music therapy embedded in the life of dementia inpatient care to help prevent and manage distress: a feasibility study to inform a future trial - Thompson, Naomi; Odell-Miller, Helen; Pointon, Chris; Underwood, Benjamin R.; Wolverson, Emma; Hunt, Rachel; Inglis, Joanne; Olawale, Abdulwarrith; Pickering, Lucy; Wilkinson, Alison; Wise, Christine; Buyukulas, Cansu; et al. (Frontiers in Psychiatry, 2025)
IntroductionMental health dementia wards in the National Health Service (NHS) in the UK provide specialist care for people with dementia experiencing acute levels of distress. There is little research into these settings, but music therapy may reduce distress in the short term. This co-designed, complex intervention development study aimed to test the feasibility of delivering a standardised music therapy protocol (MELODIC: Music therapy Embedded in the Life Of Dementia Inpatient Care) on these wards and the suitability of the research methods.MethodsThe MELODIC intervention aims to support the personalised use of music to prevent and manage distress through: 1) embedding a music therapist in the multidisciplinary team, 2) delivering clinical music therapy sessions, 3) developing musical care plans for each patient, 4) and training and support for staff and families to implement care plans. Two NHS mental health dementia wards with differing experience of music therapy were recruited purposively. All patients, families and staff were eligible to participate subject to written consent. The intervention was delivered over four weeks. The interventionist kept a diary recording all interactions with patients, staff and families to measure treatment adherence. Questionnaires reporting patient, family and staff outcomes were collected twice before and twice after intervention delivery. Routinely collected data were gathered and interviews conducted post-intervention.ResultsThe MELODIC intervention was acceptable with high levels of treatment adherence. The research methods were feasible with recruitment targets met (including 28 patients, 13 family members, 48 staff members) and all requested data collected with high levels of data completeness. Quantitative data showed no increase in distress symptoms or reported safety incidents during the intervention period. Interventionist diaries and qualitative data supported intervention refinement.ConclusionIn a highly complex setting caring for some of the most vulnerable patients in the NHS it was possible to co-design and deliver a novel music therapy intervention. The research methods were feasible and acceptable. This protocolised intervention should be tested for clinical effectiveness in a controlled trial.RegistrationISRCTN86317609